A model of the interplay between leadership styles, culture and digital transformation - Thembi Mashinini; Tebogo Sethibe (South African Journal of Information Management)
Background: Leaders play a crucial role in driving digital transformation (DT), with their leadership style either facilitating or hindering its successful implementation.